Care Orders in Child Protection: A Human-Rights Based Approach - Agyare, Patrick (Technium Social Sciences Journal, 2026)
This paper develops a thorough doctrinal and analytical framework for assessing the conditions that justify care orders in child-protection practice. It maps substantive and procedural thresholds for compulsory removal by integrating core human rights standards, statutory criteria, and recurring patterns from international jurisprudence, thereby constructing a coherent taxonomy of requirements. The framework is based on three core principles: necessity, proportionality, and the child’s best interests. It also explains how these principles work at different points in the decision-making process, such as when assessing the initial risk, considering supportive and less intrusive responses, setting evidentiary thresholds for removal, and reviewing and overseeing the process after removal. The analysis sets out a structured, multi-factor necessity test that combines objective risk indicators, the availability and adequacy of family-support interventions, and the temporal and evidentiary conditions needed to justify removing a child from parental care. Procedural protections are treated in parallel: the paper specifies standards for timely notice, meaningful participation by the child and family, access to independent representation, and adjudicative review proportionate to the seriousness of state intervention. The framework illustrates the relationship between protective measures and family preservation, demonstrating how proportionality serves as a balancing mechanism that constrains discretionary authority and administrative practices. Comparative jurisprudential patterns are synthesized to substantiate recurring solutions, without imposing rules tailored to specific jurisdictions. The resulting model improves predictability, supports consistent decision-making, and identifies targeted reforms to align protection goals with rights-based constraints on state action. It provides practical guidance for lawmakers, child-protection practitioners, and adjudicators by mapping decision points, evidentiary benchmarks, and remedial pathways, thereby informing evidence-based reform, strengthening accountability, and reducing arbitrary or disproportionate removals while preserving family life where possible.